Efectos de la nulidad de algunos artículos del decreto 4433 de 2004, en la asignación de retiro de los miembros de las Fuerzas Militares (2015)
The present research is to develop an analysis about the impact caused by the decree of nullity of the State Council on Article 14 of Decree 4433 of 2004. As this article retired law clearly violates the principle is legitimate expectations, which must be a postulate of special protection for the state, taking into account the presumed good faith of managed and generally any personal rights to citizens. in the case under investigation, it is achieved at an inconvenient evidence that the group of officers and NCOs who consolidated his right to retirement allowance, and had a length of service of between 24 and 29 years, legitimately acquired the right to they recognize an addition to their basic allocation 2% for each year of service, in addition to the 24 years without this percentage exceeded 95%, and decreed the nullification and withdraw this standard spectrum of legal rights were affected and at both the principle of legitimate expectations that attended them is broken and should be guaranteed by the administration.